Core training and motion capacity: a study on joint range in amateur soccer - Osman Yılmaz (Turkish Journal of Kinesiology, 2023)
This study investigated the effects of core training on functional movement capacity and range of motion in amateur soccer players. Twenty-nine amateur male volunteer soccer players participated in the study, including the experimental group (n = 15; age = 20.13 ± 1.55) and the control group (n = 14; age = 19.39 ± 1.08). The assumption of normality was made by employing the Kolmogorov-Smirnov test. The independent sample t-test was employed due to the normal distribution of the data. Statistically significant differences were observed between the groups in FMS, hip extension right-left, hip abduction right-left, hip internal rotation left, hip external rotation right-left, shoulder hyperextension right-left, ankle dorsiflexion right-left, and ankle plantar flexion right-left (P<0.05). No significant differences were found in the right-left knee flexion, right-left hip flexion, and right hip external rotation (P>0.05). According to the results of the study, core training improved FMS, hip extension right-left, hip abduction right-left, hip internal rotation left, hip external rotation right-left, shoulder hyperextension right-left, ankle dorsiflexion right-left, and ankle plantar flexion right-left range of motion parameters. These results suggest that including core training in the program is highly effective in improving the FMS and ROM in young soccer players.